2021
DOI: 10.3390/bioengineering8120216
|View full text |Cite
|
Sign up to set email alerts
|

The Interventricular Septum Is Biomechanically Distinct from the Ventricular Free Walls

Abstract: The interventricular septum contributes to the pumping function of both ventricles. However, unlike the ventricular wall, its mechanical behavior remains largely unknown. To fill the knowledge gap, this study aims to characterize the biaxial and transmural variation of the mechanical properties of the septum and compare it to the free walls of the left and right ventricles (LV/RV). Fresh hearts were obtained from healthy, adult sheep. The septal wall was sliced along the mid-line into two septal sides and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Animal studies that examined the transmural features of the IVS reported that the myofiber angle shifted from a longitudinal orientation on the LV-side to a circumferential orientation in the midwall, and then back to a longitudinal orientation on the RV-side of the septum. The main transmural change in the septum was related to the orientation of the myofibers (anisotropy), but not to the mechanical properties or tissue composition [ 9 ].…”
Section: Ivs Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies that examined the transmural features of the IVS reported that the myofiber angle shifted from a longitudinal orientation on the LV-side to a circumferential orientation in the midwall, and then back to a longitudinal orientation on the RV-side of the septum. The main transmural change in the septum was related to the orientation of the myofibers (anisotropy), but not to the mechanical properties or tissue composition [ 9 ].…”
Section: Ivs Structurementioning
confidence: 99%
“…During systole the IVS thickens and moves towards the LV after the onset of electrical depolarization followed by a brief ‘shudder’ at end systole, whereas during diastole it returns to its original thickness and position [ 16 ]. The IVS sides are significantly softer than their corresponding ventricular free walls, and the collagen content is less than that of the ventricular walls [ 9 ]. Moreover, at low strains, there is similar anisotropic behavior between the two sides, whereas at high strains, both sides are isotropic.…”
Section: Ivs Functionmentioning
confidence: 99%
“…The root mean square (RMS) was calculated to assess the fitting results. Finally, the anisotropic parameter K and elasticity at zero load in two directions ( and ) were calculated as described in previous studies ( Matsumoto et al, 2009 ; Javani et al, 2016 ; Nguyen-truong et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, those prior investigations are limited to a stiffness range (0.5–200 kPa) that do not encompass the complete range of RV tissue stiffness obtained from rat and ovine ex vivo mechanical tests (with the average tensile moduli of healthy and pressure-overloaded RVs ranging from ones to thousands of kPa). ,, Because of the nonlinear elastic behavior ( i.e. , nonlinear stress–strain curves) of cardiovascular tissues, ,, it is imperative to include the MSC response to substrate stiffness at higher physiological strains occurred during diastole to fully evaluate the MSC function related to specific tissue mechanical environments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the myocardium tissue is anisotropic. , This means that the tissue elasticity is different in different directions. It has been noted that the RV anisotropy (stronger fiber alignment) increases with pressure overload in the remodeling process .…”
Section: Introductionmentioning
confidence: 99%